Selecting an optimal set of keyword for search engine advertising - Hur, Minhoe; Han, Songwon; Kim, Hongtae; Cho, Sungzoon (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Online advertisers who want their website to be shown in the web search pages need to bid for relevant keywords. Selecting such keywords in advertising is challenging because they need to find relevant keywords of different click volumes and costs. Recent works focused on merely generating a list of words by using semantic or statistical methodologies. However, limited previous studies do not guarantee that those keywords will be used by customers and subsequently provide large traffic volume with lower costs. In this study, we propose a novel approach of generating relevant keywords by combining search log mining and proximity-based approach. Subsequently the optimal set of keywords with a higher volume while minimizing costs was determined. Experiment results show that our method generate an optimal set of keywords that are not only accurate, but also attract more click volume with less cost.